STRATEGY MARKETING DEVELOPMENT OF UMKM (CASE STUDY IN BOYOLALI DISTRICT-CENTRAL JAVA) - Natalia Arta Malau; Teguh Pamuji Tri Nur H (Universitas 17 Agustus 1945 Semarang, 2023)
The role of the MSME sector is very important for the economic growth of a region. Where this sector reflects the local economy, a region and as a driving force for the regional economy. The existence of the Covid 19 pandemic has caused MSMEs actors to have new challenges and problems, regarding marketing in the form of digitalization. Therefore, a strategy is needed, which is able to answer these problems. This MSME Marketing Development Strategy is to see the types and characteristics of MSMEs, potentials and problems as well as strategies for handling them. The case of this research is MSMEs Boyolali Regency. The results of this study are SWOT analysis, which requires MSME marketing activities based on MSME digitization through increased product marketing through Social Media and E-Commerce.